A randomized, feasibility trial of an exercise and nutrition‐based rehabilitation programme (ENeRgy) in people with cancer. Issue 6 (5th October 2021) - Hall, Charlie C.; Skipworth, Richard J.E.; Blackwood, Honor; Brown, Duncan; Cook, Jane; Diernberger, Katharina; Dixon, Elizabeth; Gibson, Valerie; Graham, Catriona; Hall, Peter; Haraldsdottir, Erna; Hopkinson, Jane; et al.
Abstract: Background: Despite rehabilitation being increasingly advocated for people living with incurable cancer, there is limited evidence supporting efficacy or component parts. The progressive decline in function and nutritional in this population would support an approach that targets these factors. This trial aimed to assess the feasibility of an exercise and nutrition based rehabilitation programme in people with incurable cancer. Methods: We randomized community dwelling adults with incurable cancer to either a personalized exercise and nutrition based programme (experimental arm) or standard care (control arm) for 8 weeks. Endpoints included feasibility, quality of life, physical activity (step count), and body weight. Qualitative and health economic analyses were also included. Results: Forty‐five patients were recruited (23 experimental arm, 22 control arm). There were 26 men (58%), and the median age was 78 years (IQR 69–84). At baseline, the median BMI was 26 kg/m 2 (IQR: 22–29), and median weight loss in the previous 6 months was 5% (IQR: −12% to 0%). Adherence to the experimental arm was >80% in 16/21 (76%) patients. There was no statistically significant difference in the following between trial arms: step count − median % change from baseline to endpoint, per trial arm (experimental −18.5% [IQR: −61 to 65], control 5% [IQR: −32 to 50], P = 0.548); weight − median % change from baseline to endpoint, per trial arm (experimental 1%[IQR: −3 to 3], control −0.5% [IQR: −3 to 1], P = 0.184); overall quality of life − median % change from baseline to endpoint, per trial arm (experimental 0% [IQR: −20 to 19], control 0% [IQR: −23 to 33], P = 0.846). Qualitative findings observed themes of capability, opportunity, and motivation amongst patients in the experimental arm. The mean incremental cost of the experimental arm versus control was £‐319.51 [CI −7593.53 to 6581.91], suggesting the experimental arm was less costly. Conclusions: An exercise and nutritional rehabilitation intervention is feasible and has potential benefits for people with incurable cancer. A larger trial is now warranted to test the efficacy of this approach.